ANALISIS PENGARUH NILAI TUKAR, TINGKAT SUKU BUNGA DAN INFLASI TERHADAP INDEKS HARGA SAHAM Studi Kasus Pada Perusahaan Properti yang Terdaftar di Bursa Efek Indonesia - Mardiyati, Umi; Rosalina, Ayi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
This study aims to analyze the effect of variable exchange rates, interest rates and inflation on share prices of listed property sector in Indonesia Stock Exchange. The population in this study is a company incorporated in the listed property sector in Indonesia Stock Exchange (BEI) for the period from 2007 to 2011. Samples obtained using purposive sampling method to obtain 48 companies. This study uses Ordinary Least Square analysis to determine the effect of independent variables on the stock price index of the listed property sector in Indonesia Stock Exchange. Based on t test, the exchange rate a significant negative effect on property sector stock price index, while the variable interest rates have a positive but not significant and variable inflation is positive but not significant effect on the property sector stock price index. Results simultaneously with the F test showed that all the independent variables significantly influence the stock price index property sector. So that only the exchange rate has an influence on stock price index of listed property sector in Indonesia Stock Exchange. Key words: Exchange rate, Interest Rates, Inflation, Stock Price Index.